130 research findings exhibited at CITREX 2012 - UMP, PNC
More than 130 research findings of Universiti Malaysia Pahang (UMP) were displayed at the Creation, Innovation, Technology and Research Exposition Competition (CITREX 2012) held at its Sports Complex on March 28, 2012.